Does Demography Determine Democratic Attitudes? - Rainer Kotschy; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper presents new evidence on how demography affects democratic attitudes in Western democracies. Using individual survey responses, the empirical analysis disentangles age from cohort patterns and other contemporaneous economic and political influences that shape democratic attitudes. The results reveal that support for democracy increases with age and is lower for more recent birth cohorts. These patterns are more pronounced in Western democracies than in the former Eastern bloc and in other countries around the world. Additional findings document that demography's effect partly captures heterogeneity in experiences with democracy, and that socioeconomic factors impact democratic attitudes.
Keywords: D72; O17; O43; P48; 330; support for democracy; age-periods-cohort models; population aging; demographic composition; stability of democracy; modernization hypothesis